Prevalence of babesiosis in bovines of India: a meta-analytical approach for 30 years (1990–2019) - Udipta Borthakur; Med Ram Verma; Yash Pal Singh; Sanjay Kumar; Dinesh Kumar; Yogesh Chandrakant Bangar; Khan Sharun; Kuldeep Dhama (Veterinary Quarterly, 2023)
AbstractBackground India has a massive population of bovines, which makes the framework of the economy mainly relying on milk and meat production. Parasitic diseases such as babesiosis are detrimental to bovines by decreasing animal welfare and production efficiency.Aim Performing a meta-analysis of the prevalence of babesiosis over 30 years viz 1990 to 2019 within India to pool out individual studies from different country regions.Material and methods The studies were reviewed thoroughly to assess the quality, and it was done by following the preferred reporting items for systematic review and meta-analysis (PRISMA) and MOOSE protocols. The prevalence of babesiosis in cattle and buffaloes was calculated using meta-analysis tools using R-software and Q Statistics.Results The systematic review and meta-analysis performed on 47 studies among bovine, 48 studies among cattle, and 13 studies among buffaloes revealed the (pooled) prevalence of babesiosis in India as 10.9% (6.3%–18.2%; Q = 5132.03, d.f. = 46, P < 0.001), 11.9% (6.9%–19.8%; Q = 5060.2, d.f.=47, P < 0.001), and 6.0% (2.6%–13.2%; Q = 500.55, d.f.=12, P < 0.001), respectively, which provides a rather exact scenario of the prevalence of this haemoparasitic disease across the country. In addition, cattle were having higher risk of babesiosis than buffalo.Conclusion The findings from the meta-analysis showed that the disease is prevalent across the country, and that bovines are highly affected by it.Clinical relevance Appropriate prevention and control measures should be taken to mitigate this disease and enhance welfare and production performances of bovines.